Underground warehouses for food storage in the Dolomites (Eastern alps – Italy) and energy efficiency. (August 2020) - Galgaro, Antonio; Dalla Santa, Giorgia; Cola, Simonetta; Cultrera, Matteo; De Carli, Michele; Conforti, Fabrizio; Scotton, Paolo; Viesi, Diego; Fauri, Maurizio
Highlights: A fruitful economic agreement between a mining industry and food production company. The mine geological setting creates favorable condition for underground warehouses. The dolomitic rock mass thermal behavior is described by a Finite Element Model. The model is based on direct thermal conductivity measurements and monitoring data. Compared to a surface deposit, the savings of specific energy consumption is 22% Abstract: Underground food storage represents an interesting solution to the increasing demand for new food storage space, combining this demand with sustainable land exploitation. It also reduces the energy demand for food conservation, therefore limiting storage costs and greenhouse gas emissions. Moreover, atmospheric conditions can be easily controlled in underground warehouses, ensuring optimal long-term maintenance of the stored food. This paper presents a case study located in the Western Dolomites (Val Di Non, Trento, Italy), where mining activity is followed by the creation of storage space not only for food, but also for groundwater and a data hosting center. After the extraction of the dolomitic rock used in construction, underground excavated spaces are converted into warehouses, whose storage capability is improved once the inner surfaces have been protected by a gas-proof mineral hydraulic lime material, developed for this purpose. The thermal behavior of the rock mass over the first few years is analyzed by means of a Finite Element Model and compared with on-site monitoring data. Laboratory measurements of the thermal properties of the dolomite rock and the temperature data registered in the field permitted the development of a preliminary numerical model, in order to describe the heat exchange between the cavern and the rock mass and supply data to support future developments. Finally, the specific energetic consumption is compared with the one required by an aboveground deposit.